Cobalt Demand for Automotive Electrification in China: Scenario Analysis Based on the Bass Model - Shi, Qing (Frontiers in Energy Research, 2022)
With accelerating automotive electrification process, quantitative analysis of cobalt demand becomes a critical issue in China. How much cobalt is expected to be needed from 2021 to 2030 to support a smooth automotive electrification in China? This study aims to answer this question comprehensively by examining the responses of annual cobalt demand to variations in electric vehicle sales, battery capacity factors, and cobalt substitution effects, which has not been fully explored in previous literature. Scenario analysis based on the Bass model is adopted and historical data from 2012 to 2020 are used for this study. The results show that (1) the peak annual cobalt demand will reach 35.58—126.97 kt/year during 2021-2030; (2) cobalt demand is expected to decline by 14.29% if the market share of ternary lithium-ion battery decreases by 10%; (3) while cobalt substitution can reduce the demand substantially, it cannot offset the growth of cobalt demand driven by the increasing EV sales and battery capacity. These results provide a knowledge base for policy suggestions to manage the cobalt demand—supply balance in China better.